Untangling the gut-brain axis: the relevance of gut microbiota in alcohol use disorder - Tommaso Dionisi; Valeria Maccauro; Giovanni Addolorato (Nutrimentum et Curae)
Alcohol Use Disorder (AUD) is a chronic health problem marked by an inability to cease or control alcohol use. This disorder significantly disrupts physiological functions, negatively impacting various body systems and posing significant detriment to both individual and societal health. Recent studies have shown that AUD has a significant impact on the Gut-Brain Axis (GBA), which involves a complex interplay of neuroimmunoendocrine and metabolic pathways.